Optimizing Target Costing Implementation for Cost Efficiency and Increasing Product Profits - Sangkala, Masnawaty (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is a type of qualitative research using a case study approach. The data sources used in this research are primary and secondary data. Primary data consists of data obtained from field observations and informant interviews. Meanwhile, secondary data consists of data that has been obtained from the company which is then reprocessed by researchers. The data analysis and processing used in this research is to obtain research supporting data and then process it using the target costing method until finally conclusions can be drawn from the research process. The results of this research indicate that the application of the target costing method is effective for efficient production costs by obtaining a difference of Rp. 340,206,650 of the total production costs carried out before and after implementing the target costing method of Rp. 516,244,150 and Rp. 176, 037, 500. Then there was an increase in product profits by looking at the difference between income in 2020 and 2021 which had increased by 71.4% as well as implementing additional alternatives by making changes to the selling price combined with value engineering methods so that it is able to maximize profits in accordance with initial planning.